Carbon nanotube surface modification method and application thereof in rubber composite material
By introducing hydroxy functional groups on the surface of carbon nanotubes and carrying out specific chemical reactions to generate polymers with self-healing functions, the dispersion and interface compatibility of carbon nanotubes in rubber composite materials are solved, and the mechanical properties and durability of the material are improved.
Patent Information
- Application Number
- CN202510811211.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-08-26
AI Technical Summary
Carbon nanotubes have poor dispersion in rubber composite materials, weak interface compatibility with rubber matrix, and lack self-healing function.
The hydroxyl functional groups were introduced on the surface of the carbon nanotubes by hydroxylation, and maleic anhydride, para-olefin aniline and furyl groups were introduced on the surface of the carbon nanotubes through copolymerization, amide reaction and Diels-Alder reaction to form a polymer with self-healing function, and then chemically bonded with the polymer rich in carboxyl functional groups.
It improves the dispersion and interface compatibility of carbon nanotubes in rubber matrix, enhances the mechanical properties and self-healing functions of the material, and improves the durability and service life of the material.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon nanotubes, and in particular to a carbon nanotube surface modification method and application thereof in rubber composite materials. Background Art
[0002] In the field of rubber composites, carbon nanotubes (CNTs) have been widely studied and applied due to their excellent mechanical and electrical properties. However, the dispersion of CNTs in the rubber matrix has always been a key issue. Due to the high surface energy of CNTs, they tend to aggregate in the rubber matrix, resulting in heterogeneity in the material properties. In addition, the interfacial compatibility between CNTs and the rubber matrix is weak, which limits the effective transfer of stress and thus affects the overall performance of the composite. Although studies have attempted to improve these problems through methods such as surface treatment, current technical means are still unable to completely solve the dispersion and interfacial compatibility problems of CNTs in rubber composites. Therefore, developing an effective surface modification method for CNTs to improve their dispersion and interfacial compatibility in rubber composites is of great significance for improving the performance of rubber composites. Summary of the Invention
[0003] In view of the above shortcomings of the existing technology, the present invention provides a carbon nanotube surface modification method to solve the technical problems of poor dispersion of traditional carbon nanotubes in rubber composites, weak interfacial compatibility with the rubber matrix, and lack of self-repairing function after modification.
[0004] In order to achieve the above purpose, the technical solution adopted by the present invention is: A method for modifying the surface of carbon nanotubes, comprising the following steps: S1: subjecting carbon nanotubes to hydroxylation treatment to introduce hydroxyl functional groups onto their surfaces, thereby obtaining hydroxylated carbon nanotubes.
[0005] S2: Maleic anhydride and para-olefin aniline are added to a reactor in proportion and heated to carry out a copolymerization reaction; acyl chloride furan is added to the above copolymerization reaction system to carry out an amide reaction under nitrogen protection; the reaction product is then dissolved in a solvent, and maleic anhydride is then added to carry out a Diels-Alder reaction to obtain a polymer with self-healing function.
[0006] In step S2, the anhydride group of maleic anhydride and the amino active sites of para-olefin aniline are first introduced through the copolymerization reaction of maleic anhydride and para-olefin aniline. The introduction of para-olefin aniline is mainly to introduce amino groups on the polymer chain, providing reactive sites for the subsequent amide reaction. The anhydride group of maleic anhydride provides a precursor for the subsequent hydrolysis reaction in step S3, which can be converted into carboxyl groups after hydrolysis, further enhancing the chemical bonding with the hydroxylated carbon nanotubes in step S1. Next, acyl chloride furan is added to carry out an amide reaction to introduce furan groups. The introduction of furan groups improves the mechanical strength and thermal stability of the polymer, while providing a diene structure for the subsequent Diels-Alder reaction. Finally, maleic anhydride is added again to carry out a Diels-Alder reaction to generate a reversible six-membered ring structure, realizing the self-healing function of the polymer. This six-membered ring structure reversibly decomposes at an appropriate temperature, allowing the polymer to gain fluidity to fill the damaged parts of the material, and then reforms upon cooling to restore the material properties.
[0007] S3: dispersing the polymer obtained in step S2 in water, adding an alkaline solution to carry out a hydrolysis reaction, and adjusting the pH to 4-7 with an acidic solution after the reaction to obtain a polymer rich in carboxyl functional groups.
[0008] S4: dispersing the hydroxylated carbon nanotubes obtained in step S1 in a solvent, adding the polymer rich in carboxyl functional groups obtained in step S3, and uniformly adsorbing the polymer on the surface of the carbon nanotubes by ultrasonic treatment to undergo chemical bonding reaction, and finally drying to obtain surface-modified carbon nanotubes.
[0009] As a preferred technical solution, the hydroxylation treatment steps are: dispersing carbon nanotubes in a mixed solution containing concentrated sulfuric acid and concentrated nitric acid, performing ultrasonic treatment, then performing hydrothermal reaction, and finally obtaining hydroxylated carbon nanotubes by washing and drying.
[0010] As a preferred technical solution, the para-olefin aniline is at least one of 4-(vinyloxy)-aniline, 4-(allyloxy)aniline, 4-(3-butene-1-yloxy)aniline, and 4-[(2-methyl-2-propylene-1-yl)oxy]aniline.
[0011] As a preferred technical solution, the acyl chloride furan is at least one of (5-methyl-2-furyl) (oxo) acetyl chloride, (5-ethoxy-2-furyl) (oxo) acetyl chloride, [5-(methoxymethyl)-2-furyl] (oxo) acetyl chloride, and 5-methyl-2-furoyl chloride.
[0012] As a preferred technical solution, in step S2, the molar ratio of maleic anhydride to para-olefin aniline is 1:1-2.
[0013] As a preferred technical solution, in step S2, the reaction temperature of the copolymerization reaction is 120-140°C, and the reaction time is 4-8 hours; the reaction temperature of the amide reaction is 80-100°C, and the reaction time is 2-4 hours; the reaction temperature of the Diels-Alder reaction is 100-120°C, and the reaction time is 3-6 hours.
[0014] As a preferred technical solution, in step S3, the alkaline solution is sodium hydroxide solution and / or potassium hydroxide solution, and the acidic solution is hydrochloric acid solution and / or sulfuric acid solution; the temperature of the hydrolysis reaction is 60-80°C, and the time is 2-4 hours.
[0015] As a preferred technical solution, in step S4, the ultrasonic power of the ultrasonic treatment is 300-400W, and the time is 1 to 3 hours.
[0016] As a preferred technical solution, in step S4, the mass ratio of the hydroxylated carbon nanotubes to the polymer rich in carboxyl functional groups is 1:1-5.
[0017] Another aspect of the present invention is to provide an application of a carbon nanotube surface modification method in a rubber composite material. The rubber composite material includes carbon nanotubes obtained by the above carbon nanotube surface modification method, a rubber matrix, a vulcanizing agent, and an accelerator.
[0018] Beneficial effects of the present invention: The carbon nanotube surface modification method of the present invention effectively improves the dispersibility of carbon nanotubes in a rubber matrix by introducing a polymer rich in carboxyl functional groups onto the surface of carbon nanotubes, reduces agglomeration, and ensures uniform distribution and full reinforcing effect. The carboxyl groups on the polymer chain undergo an esterification reaction with the hydroxyl groups on the surface of the carbon nanotubes, forming a strong chemical bond and enhancing the binding force. At the same time, the aromatic groups and furan groups on the main chain and side chains of the polymer interact well with the rubber matrix, further improving interfacial compatibility, promoting stress transfer, and enhancing mechanical properties. In addition, the Diels-Alder reaction of the furan groups with maleic anhydride generates a reversible six-membered ring structure, which gives the rubber composite a self-repairing function, significantly improves durability and service life, and reduces maintenance costs. The aromatic groups and furan groups on the polymer chain have high thermal stability, reduce thermal decomposition and thermal oxidation at high temperatures, and extend service life. The introduction of groups such as maleic anhydride and para-olefin aniline significantly enhances the mechanical strength of the polymer, improves tensile strength and compressive strength, and meets the requirements of high-performance applications. In summary, the modification method of the present invention imparts the rubber composite material with excellent comprehensive properties such as self-repairing function, thermal stability and mechanical strength, which better meets the needs of high-performance applications. DETAILED DESCRIPTION
[0019] The following description is intended to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are merely examples, and those skilled in the art may conceive of other obvious variations.
[0020] Example 1 The carbon nanotube surface modification method of this embodiment includes the following steps: S1: The carbon nanotubes are subjected to hydroxylation treatment to introduce hydroxyl functional groups on their surfaces to obtain hydroxylated carbon nanotubes; the steps of the hydroxylation treatment are as follows: 15 g of carbon nanotubes are dispersed in 500 mL of a mixed solution containing concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), ultrasonically treated (ultrasonic power 300 W, treatment time 2 h), followed by hydrothermal reaction (reaction temperature 180°C, reaction time 12 h), and finally the hydroxylated carbon nanotubes are obtained by washing and drying.
[0021] S2: 10 g of maleic anhydride and 20 g of 4-(vinyloxy)-aniline are added to a reactor in proportion and heated for copolymerization; the reaction temperature of the copolymerization reaction is 130°C and the reaction time is 6 hours; 25.8 g of (5-methyl-2-furyl) (oxy)acetyl chloride is added to the above copolymerization reaction system to carry out amide reaction under nitrogen protection; the reaction temperature of the amide reaction is 90°C and the time is 3 hours, and an appropriate amount of triethylamine is added as a catalyst during the reaction; the reaction product is then dissolved in an appropriate amount of acetone solvent, and then 15 g of maleic anhydride is added to carry out Diels-Alder reaction, and the reaction temperature of the Diels-Alder reaction is 110°C and the time is 4 hours; a polymer with self-healing function is obtained.
[0022] S3: Disperse 25 g of the polymer obtained in step S2 in 500 mL of water, add 50 mL of sodium hydroxide solution (concentration 1 mol / L) for hydrolysis reaction, and adjust the pH to 6 with hydrochloric acid solution (concentration 0.1 mol / L) after the reaction to obtain a polymer rich in carboxyl functional groups; the hydrolysis reaction temperature is 70°C and the time is 2 h.
[0023] S4: The hydroxylated carbon nanotubes obtained in step S1 are dispersed in an ethyl acetate solvent, and the carboxyl functional group-rich polymer obtained in step S3 is added, wherein the mass ratio of the hydroxylated carbon nanotubes to the carboxyl functional group-rich polymer is 1:2. The polymer is uniformly adsorbed on the surface of the carbon nanotubes by ultrasonic treatment to perform a chemical bonding reaction (an appropriate amount of concentrated sulfuric acid can be added dropwise during the reaction to promote the reaction). The ultrasonic power of the ultrasonic treatment is 350 W, and the time is 2 h. Finally, the surface-modified carbon nanotubes are obtained by drying.
[0024] Application Example 1 This application example describes the use of a carbon nanotube surface modification method in a rubber composite material. The rubber composite material comprises 10g of carbon nanotubes obtained using the carbon nanotube surface modification method described above, 100g of a rubber matrix (natural rubber), 2g of a vulcanizing agent (sulfur), and 1g of an accelerator (N-nitrosodiphenylamine). These materials are mixed uniformly and then vulcanized (vulcanization temperature: 145°C, vulcanization time: 20 minutes) to obtain the rubber composite material.
[0025] Example 2 The carbon nanotube surface modification method of this embodiment includes the following steps: S1: The carbon nanotubes are subjected to hydroxylation treatment to introduce hydroxyl functional groups on their surfaces to obtain hydroxylated carbon nanotubes; the steps of the hydroxylation treatment are as follows: 8 g of carbon nanotubes are dispersed in 500 mL of a mixed solution containing concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), ultrasonically treated (ultrasonic power 350 W, treatment time 1.5 h), followed by hydrothermal reaction (reaction temperature 190°C, reaction time 10 h), and finally the hydroxylated carbon nanotubes are obtained by washing and drying.
[0026] S2: 10 g of maleic anhydride and 23 g of 4-(allyloxy)aniline were added to a reactor in proportion and heated for copolymerization; the reaction temperature of the copolymerization reaction was 125°C and the reaction time was 5 h; 30 g of (5-ethoxy-2-furyl)(oxy)acetyl chloride was added to the above copolymerization reaction system to carry out an amide reaction under nitrogen protection; the reaction temperature of the amide reaction was 85°C and the time was 4 h, and an appropriate amount of triethylamine was added as a catalyst during the reaction; the reaction product was then dissolved in an appropriate amount of acetone solvent, and 15 g of maleic anhydride was added to carry out a Diels-Alder reaction, and the reaction temperature of the Diels-Alder reaction was 105°C and the time was 5 h; a polymer with self-healing function was obtained.
[0027] S3: 20 g of the polymer obtained in step S2 was dispersed in 400 mL of water, and 40 mL of potassium hydroxide solution (concentration 1 mol / L) was added for hydrolysis reaction. After the reaction, the pH was adjusted to 5 with hydrochloric acid solution (concentration 0.1 mol / L) to obtain a polymer rich in carboxyl functional groups; the hydrolysis reaction temperature was 65°C and the time was 3 h.
[0028] S4: dispersing the hydroxylated carbon nanotubes obtained in step S1 in a solvent, adding the polymer rich in carboxyl functional groups obtained in step S3, wherein the mass ratio of the hydroxylated carbon nanotubes to the polymer rich in carboxyl functional groups is 1:3, and performing ultrasonic treatment so that the polymer is uniformly adsorbed on the surface of the carbon nanotubes for chemical bonding reaction, wherein the ultrasonic power of the ultrasonic treatment is 300 W and the time is 3 hours, and finally obtaining surface-modified carbon nanotubes by drying.
[0029] Application Example 2 This application example describes the use of a carbon nanotube surface modification method in a rubber composite material. The rubber composite material comprises 10g of carbon nanotubes obtained using the carbon nanotube surface modification method described above, 100g of a rubber matrix (natural rubber), 2g of a vulcanizing agent (sulfur), and 1g of an accelerator (N-nitrosodiphenylamine). These materials are mixed uniformly and then vulcanized (vulcanization temperature: 145°C, vulcanization time: 20 minutes) to obtain the rubber composite material.
[0030] Example 3 The carbon nanotube surface modification method of this embodiment includes the following steps: S1: The carbon nanotubes are subjected to hydroxylation treatment to introduce hydroxyl functional groups on their surfaces to obtain hydroxylated carbon nanotubes; the steps of the hydroxylation treatment are as follows: 12 g of carbon nanotubes are dispersed in 500 mL of a mixed solution containing concentrated sulfuric acid and concentrated nitric acid (volume ratio of 3:1), ultrasonically treated (ultrasonic power 300 W, treatment time 2 h), followed by hydrothermal reaction (reaction temperature 180°C, reaction time 12 h), and finally the hydroxylated carbon nanotubes are obtained by washing and drying.
[0031] S2: 10 g of maleic anhydride and 24.5 g of 4-[(2-methyl-2-propen-1-yl)oxy]aniline were added to the reactor in proportion and heated for copolymerization; the reaction temperature of the copolymerization reaction was 140°C and the reaction time was 4 hours; 22 g of 5-methyl-2-furoyl chloride was added to the above copolymerization reaction system and an amide reaction was carried out under nitrogen protection; the reaction temperature of the amide reaction was 100°C and the time was 2 hours, and an appropriate amount of triethylamine was added as a catalyst during the reaction; the reaction product was then dissolved in an appropriate amount of acetone solvent, and 15 g of maleic anhydride was added to carry out a Diels-Alder reaction, and the reaction temperature of the Diels-Alder reaction was 120°C and the time was 3 hours; a polymer with self-healing function was obtained.
[0032] S3: 30 g of the polymer obtained in step S2 was dispersed in 500 mL of water, and 60 mL of potassium hydroxide solution (concentration 1 mol / L) was added for hydrolysis reaction. After the reaction, the pH was adjusted to 5.5 with hydrochloric acid solution (concentration 0.1 mol / L) to obtain a polymer rich in carboxyl functional groups; the hydrolysis reaction temperature was 75°C and the time was 2.5 h.
[0033] S4: dispersing the hydroxylated carbon nanotubes obtained in step S1 in a solvent, adding the polymer rich in carboxyl functional groups obtained in step S3, wherein the mass ratio of the hydroxylated carbon nanotubes to the polymer rich in carboxyl functional groups is 1:4, and performing ultrasonic treatment so that the polymer is uniformly adsorbed on the surface of the carbon nanotubes for chemical bonding reaction, wherein the ultrasonic power of the ultrasonic treatment is 400 W and the time is 2 h, and finally obtaining surface-modified carbon nanotubes by drying.
[0034] Application Example 3 This application example describes the use of a carbon nanotube surface modification method in a rubber composite material. The rubber composite material comprises 10g of carbon nanotubes obtained using the carbon nanotube surface modification method described above, 100g of a rubber matrix (natural rubber), 2g of a vulcanizing agent (sulfur), and 1g of an accelerator (N-nitrosodiphenylamine). These materials are mixed uniformly and then vulcanized (vulcanization temperature: 145°C, vulcanization time: 20 minutes) to obtain the rubber composite material.
[0035] Example 4 The raw material composition and preparation steps of the carbon nanotube surface modification method of this embodiment are essentially the same as those of Example 1, except that 4-(vinyloxy)-aniline is replaced with 4-(3-buten-1-yloxy)aniline as the para-olefin aniline. The raw material composition and preparation steps of the rubber composite material of Application Example 4 are the same as those of Application Example 1, except for the carbon nanotubes.
[0036] Example 5 The raw material composition and preparation steps of the carbon nanotube surface modification method of this embodiment are essentially the same as those of Example 1, except that the acyl furan chloride is replaced with [5-(methoxymethyl)-2-furyl](oxo)acetyl chloride. The raw material composition and preparation steps of the rubber composite material of Application Example 5 are the same as those of Application Example 1, except for the carbon nanotubes.
[0037] Comparative Example 1 The raw material composition and preparation steps of the carbon nanotube surface modification method in this comparative example are essentially the same as those in Example 1, except that 4-(vinyloxy)-aniline is not added in step S2. The raw material composition and preparation steps of the rubber composite material in Comparative Application Example 1 are the same as those in Application Example 1, except for the carbon nanotubes.
[0038] Comparative Example 2 The raw material composition and preparation steps of the carbon nanotube surface modification method in this comparative example are essentially the same as those in Example 1, except that (5-methyl-2-furyl)(oxo)acetyl chloride is not added in step S2. The raw material composition and preparation steps of the rubber composite material in Comparative Application Example 2 are the same as those in Application Example 1, except for the carbon nanotubes.
[0039] The rubber composite materials prepared in Application Examples 1 to 5 and Comparative Application Examples 1 to 2 were subjected to performance tests, and the performance results are shown in Table 1: Tensile strength is tested according to the national standard GB / T 528. Standard dumbbell-shaped specimens are cut from the rubber composite sample to ensure that the specimen dimensions meet the standard requirements. The specimen is mounted in the fixture of a universal testing machine. The tensile speed is set to 500 mm / min, and the machine is activated to stretch the specimen, recording the stress-strain curve. When the specimen breaks, the maximum tensile force is recorded, and the tensile strength is calculated based on the specimen's cross-sectional area.
[0040] Elongation at break is tested in accordance with the national standard GB / T 528, using the same specimens and equipment as for tensile strength testing. During the stretching process, the total elongation of the specimen from the start of stretching to fracture is recorded. Based on the specimen's original gauge length and the total elongation at fracture, the elongation is calculated using the formula: Elongation at break (%) = (Total elongation at fracture / Original gauge length) × 100.
[0041] Wear resistance was tested according to the national standard GB / T 1689. Rubber composite samples were processed into standard-sized specimens (38.1 mm long, 12.7 mm wide, and 6.35 mm thick). These were then mounted on an Akron abrasion tester at a speed of 75 r / min and subjected to a standard load (2.5 kg). After the specified abrasion time (30 minutes), the specimens were removed and weighed, and the mass loss was calculated as the wear rate.
[0042] The self-healing efficiency performance test method involves processing rubber composite samples into standard-sized specimens (50 mm long, 10 mm wide, and 2 mm thick). Artificial cracks (5 mm long and 0.5 mm wide) are then created on the surface. The samples are then placed in a designated repair environment (80°C ± 2°C) for a period of 24 hours for self-healing. After repair, the cracks are observed using a microscope or other equipment, and their size is measured. The self-healing efficiency is calculated using the formula: Self-healing efficiency (%) = (1 - crack size after repair / crack size before repair) × 100.
[0043] Thermal stability is tested according to the national standard GB / T 1634.2. Rubber composite samples are processed into standard-sized specimens (80 mm long, 10 mm wide, and 4 mm thick), placed in the sample holder of a heat deformation tester, and placed in a heating furnace at a set heating rate of 5°C / min ± 0.5°C / min. A standard load (1.8 kg) is applied to the specimen. The temperature at which the specimen deforms to a certain degree (0.25 mm) is recorded as the heat deformation temperature, which serves as a reference indicator of thermal stability.
[0044] Table 1 project Application Example 1 Application Example 2 Application Example 3 Application Example 4 Application Example 5 Comparative Application Example 1 Comparative Application Example 2 Tensile strength, MPa 25.6 26.8 27.3 26.2 25.9 20.5 21.0 Elongation at break, % 550 580 570 560 540 480 490 Wear resistance, mg 50 48 47 49 51 60 58 Self-repair efficiency, % 85 88 89 87 86 55 26 Thermal stability, ℃ 280 285 288 283 281 271 269 The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. Various changes and improvements are possible without departing from the spirit and scope of the present invention, and such changes and improvements fall within the scope of the invention as claimed.
Claims
1. A method for surface modification of carbon nanotubes, characterized in that: The method comprises the following steps: S1: hydroxylating the carbon nanotubes to introduce hydroxyl functional groups onto their surfaces to obtain hydroxylated carbon nanotubes; S2: maleic anhydride and para-olefin aniline are added to a reactor in proportion and heated to carry out a copolymerization reaction; acyl chloride furan is added to the above copolymerization reaction system to carry out an amide reaction under nitrogen protection; the reaction product is then dissolved in a solvent, and maleic anhydride is then added to carry out a Diels-Alder reaction to obtain a polymer with self-healing function; S3: dispersing the polymer obtained in step S2 in water, adding an alkaline solution to carry out a hydrolysis reaction, and adjusting the pH to 4 to 7 with an acidic solution after the reaction to obtain a polymer rich in carboxyl functional groups; S4: dispersing the hydroxylated carbon nanotubes obtained in step S1 in a solvent, adding the polymer rich in carboxyl functional groups obtained in step S3, and uniformly adsorbing the polymer on the surface of the carbon nanotubes by ultrasonic treatment to undergo chemical bonding reaction, and finally drying to obtain surface-modified carbon nanotubes.
2. The carbon nanotube surface modification method according to claim 1, wherein: The steps of the hydroxylation treatment are: dispersing the carbon nanotubes in a mixed solution containing concentrated sulfuric acid and concentrated nitric acid, performing ultrasonic treatment, then performing hydrothermal reaction, and finally washing and drying to obtain hydroxylated carbon nanotubes.
3. The carbon nanotube surface modification method according to claim 1, wherein: The para-olefin aniline is at least one of 4-(vinyloxy)-aniline, 4-(allyloxy)aniline, 4-(3-butene-1-yloxy)aniline and 4-[(2-methyl-2-propen-1-yl)oxy]aniline.
4. The carbon nanotube surface modification method according to claim 1, wherein: The furan acyl chloride is at least one of (5-methyl-2-furyl) (oxo) acetyl chloride, (5-ethoxy-2-furyl) (oxo) acetyl chloride, [5-(methoxymethyl)-2-furyl] (oxo) acetyl chloride and 5-methyl-2-furoyl chloride.
5. The carbon nanotube surface modification method according to claim 1, wherein: In step S2, the molar ratio of maleic anhydride to para-olefin aniline is 1:1-2.
6. The carbon nanotube surface modification method according to claim 1, wherein: In step S2, the reaction temperature of the copolymerization reaction is 120-140° C., and the reaction time is 4-8 hours; the reaction temperature of the amide reaction is 80-100° C., and the reaction time is 2-4 hours; and the reaction temperature of the Diels-Alder reaction is 100-120° C., and the reaction time is 3-6 hours.
7. The carbon nanotube surface modification method according to claim 1, wherein: In step S3, the alkaline solution is sodium hydroxide solution and / or potassium hydroxide solution, and the acidic solution is hydrochloric acid solution and / or sulfuric acid solution; the temperature of the hydrolysis reaction is 60-80° C., and the time is 2-4 hours.
8. The carbon nanotube surface modification method according to claim 1, wherein: In step S4, the ultrasonic treatment is performed at an ultrasonic power of 300-400 W and for a time of 1 to 3 hours.
9. The carbon nanotube surface modification method according to claim 1, wherein: In step S4, the mass ratio of the hydroxylated carbon nanotubes to the polymer rich in carboxyl functional groups is 1:1-5.
10. Application of a carbon nanotube surface modification method in rubber composite materials, characterized in that: The rubber composite material comprises carbon nanotubes obtained by the carbon nanotube surface modification method according to any one of claims 1 to 9, and also comprises a rubber matrix, a vulcanizing agent, and an accelerator.